2021
DOI: 10.1016/j.nepr.2021.103056
|View full text |Cite
|
Sign up to set email alerts
|

Training situational awareness for scrub nurses: Error recognition in a virtual operating room

Abstract: Virtual reality simulation provides interesting opportunities to train nurses in a safe environment. While the virtual operating room has proven to be a useful training tool for technical skills, it has been less studied for non-technical skills. This study aimed to assess "Error recognition in a virtual operating room", using a simulation scenario designed to improve situation awareness. Eighteen scrub-nurse students and 8 expert scrub-nurses took part in the experiment. They were immersed in a virtual operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…With the improvement of nursing education, nurses are not limited to clinical practice but also need to assist doctors to promote the rapid recovery of patients. Introducing student nurses to real situational experiences is more conducive to actively guiding their ability to discover, analyze, and solve problems independently [ 35 , 36 ], as well as to facilitating nurse clinicians' transition to the nurse educator role [ 37 ]. Studies have shown that adverse events are closely related to patient safety and care quality, but about 50% of them can be prevented [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of nursing education, nurses are not limited to clinical practice but also need to assist doctors to promote the rapid recovery of patients. Introducing student nurses to real situational experiences is more conducive to actively guiding their ability to discover, analyze, and solve problems independently [ 35 , 36 ], as well as to facilitating nurse clinicians' transition to the nurse educator role [ 37 ]. Studies have shown that adverse events are closely related to patient safety and care quality, but about 50% of them can be prevented [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…최근 수술실 간호사의 상황인식과 관련된 선행연구로는 수 술 과정 동안 소독간호사가 외과의에게 기구를 전달하는 움직 임을 통해 상황인식의 정도를 분석했던 관찰적 문화기술지연 구(observational ethnographic research) [8], 수술실에서 의 료팀의 상황인식에 영향하는 요인을 분석하는 연구 [9], 간호사 를 대상으로 상황인식과 임상의사결정에 대한 체계적 문헌고 찰 연구 [4], 간호학생들의 상황인식을 향상시키기 위해 특별한 훈련(시뮬레이션)이 필요하다는 연구 [10,11]…”
Section: 서 론unclassified
“…Virtual reality (VR) is a defined as a computer-generated reality, which creates an opportunity for learners to experience various auditory and visual stimuli experienced through specialized hardware, such as head-mounted displays (HMDs) (INACSL Standards Committee 2016 ). The implementation of VR in medicine is not new and has been used in various medical contexts, ranging from nursing, clinical psychology, hospital teamwork, anatomical discovery, surgical operational training, pre- and post-surgical training, and for augmentation, and has shown increasing potential for improving learning outcomes (Vaughan et al 2016 ; Bracq et al 2021 ; Mehrotra and Markus 2021a ).…”
Section: Introductionmentioning
confidence: 99%